Comprehensive analysis of B3 family genes in pearl millet (Pennisetum glaucum) and the negative regulator role of PgRAV-04 in drought tolerance - Wang, Yin-Hua; Ye, Xing; Zhao, Bi-Yao; Wang, Wen-Jing; Zhou, Zheng-Feng; Zhang, Xiang-Qian; Du, Juan; Song, Jian-Ling; Huang, Xiao-Ling; Ouyang, Kun-Xi; Zhong, Tian-Xiu; Liao, Fei-Xiong (Frontiers in Plant Science, 2024)
Members of the plant-specific B3 transcription factor superfamily play crucial roles in various plant growth and developmental processes. Despite numerous valuable studies on B3 genes in other species, little is known about the B3 superfamily in pearl millet. Through comparative genomic analysis, we identified 70 B3 proteins in pearl millet and categorized them into four subfamilies based on phylogenetic affiliations: ARF, RAV, LAV, and REM. We also mapped the chromosomal locations of these proteins and analyzed their gene structures, conserved motifs, and gene duplication events, providing new insights into their potential functional interactions.Using transcriptomic sequencing and real-time quantitative PCR, we determined that most PgB3 genes exhibit upregulated expression under drought and high-temperature stresses, indicating their involvement in stress response regulation. To delve deeper into the abiotic stress roles of the B3 family, we focused on a specific gene within the RAV subfamily, PgRAV-04, cloning it and overexpressing it in tobacco. PgRAV-04 overexpression led to increased drought sensitivity in the transgenic plants due to decreased proline levels and peroxidase activity. This study not only adds to the existing body of knowledge on the B3 family's characteristics but also advances our functional understanding of the PgB3 genes in pearl millet, reinforcing the significance of these factors in stress adaptation mechanisms.